2001
DOI: 10.1007/s004020000238
|View full text |Cite
|
Sign up to set email alerts
|

The musculocutaneous sural artery flap for soft-tissue coverage after calcaneal fracture

Abstract: Soft-tissue defects following calcaneal fractures can be covered in a relatively easy and safe procedure. We have modified the familiar distally based sural artery flap by lifting a part of the gastrocnemius muscle. With an inferior pedicle, this musulocutaneous flap can be rotated onto the defect on the sole of the foot and on the heel. Five patients with open fractures of the calcaneus or wound necrosis after osteosynthesis were treated with this procedure. Two defects were covered uneventfully, two flaps we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
14

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 7 publications
0
15
0
14
Order By: Relevance
“…Coverage by a sural flap (musculo-cutaneous rotational flap from the soleus) [17] was done with excellent results.…”
Section: Resultsmentioning
confidence: 99%
“…Coverage by a sural flap (musculo-cutaneous rotational flap from the soleus) [17] was done with excellent results.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] This technique has been specially applied for reconstruction of soft tissue defects complicated with osteomyelitis. Our anatomic study found that there were usually 2-3 communicating branches connecting the sural vascular axis to the gastrocnemius muscle in the 4 cm overlapping length proximal to the junction of tendon-muscle belly.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of the flap can be designed based on its pedicle and components, such as fasciocutaneous, fasciosubcutaneous, adipofascial, and fasciomyocutaneous flaps. 3 The distally based sural fasciomyocutaneous flap including a gastrocnemius muscle fragment or muscle cuff carried beneath the deep fascia was described by Al Qattan, 4 Le Fourn et al, 5 and Mueller et al 6 in 2001, respectively. The fasciomyocutaneous flap has been shown to provide bulk and high metabolic viable muscle component for repairs of the soft tissue defects complicated with osteomyelitis and/or deep dead space.…”
mentioning
confidence: 98%
“…Bei Defekten größer als 5 cm sind gestielte Muskellappen am Sprunggelenk nicht mehr einsetzbar. Ebenso wenig sind der distal gestielte Suralislappen [3,24], der Peroneallappen, der Arteria-dorsalis-pedis-Lappen, der Plantaris-medialis-Lappen oder der M. abductor digiti minimi für ausgedehnte Defekte am OSG oder Fuß geeignet [17] und sie hinterlassen nicht unwesentliche Hebedefekte [23].…”
Section: Tab 1 Freie Fasziokutane Lappenplastik Bei Talus-und Kalkanunclassified
“…Sofern die Sensibilität der gewichtstragenden Metatarsalköpfchen vorhanden ist, stellt der (Para-)Skapularlappen nach unserer Erfahrung auch eine wertvolle Möglichkeit zur Defektdeckung der Teilbelastungszone dar [2,23,24]. Hierzu zählen neben der mittleren Plantarregion der Fußrücken und der perimalleoläre Bereich (.…”
Section: Tab 1 Freie Fasziokutane Lappenplastik Bei Talus-und Kalkanunclassified